2018
DOI: 10.4081/aiua.2018.2.130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison between conventional and microdissection testicular sperm extraction for non-obstructive azoospermia: Understanding which treatment works for which patient

Abstract: Objectives: The superiority of microdissection testicular sperm extraction (mTESE) over conventional TESE (cTESE) for men with non-obstructive azoospermia (NOA) is debated. We aimed to compare the sperm retrieval rate (SRR) of mTESE to cTESE and to identify candidates who would most benefit from mTESE in a cohort of Caucasian-European men with primary couple's infertility. Material and methods: Data from 49 mTESE and 96 cTESE patients were analysed. We collected demographic and clinical data, serum levels of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…SRRs may serve as points of comparison between different operative techniques, which may help surgeons identify more efficacious approaches, as demonstrated by Bernie et al (2015) 17 . Similarly, highlighting predictors of retrieval of any testicular spermatozoa may help identify specific demographics of NOA patients and specific histopathology which are correlated with higher retrieval, as demonstrated by Maglia et al (2018) 71 . However, there is little published consensus on exactly what defines a successful sperm retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…SRRs may serve as points of comparison between different operative techniques, which may help surgeons identify more efficacious approaches, as demonstrated by Bernie et al (2015) 17 . Similarly, highlighting predictors of retrieval of any testicular spermatozoa may help identify specific demographics of NOA patients and specific histopathology which are correlated with higher retrieval, as demonstrated by Maglia et al (2018) 71 . However, there is little published consensus on exactly what defines a successful sperm retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that there are no precise and noninvasive methods for predicting whether there are testicular spermatozoa in NOA patients before mTESE [ 10 ]. Maglia et al found that the success rate of sperm retrieval in NOA patients was similar between the mTESE group and the conventional TESA group, and mTESE seemed to be more beneficial for patients over 35 years of age and with high FSH value [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“… 6 7 Many studies showed that the sperm acquisition rate of Micro-TESE is higher than that of traditional testicular sperm extraction. 8 For example, Schlegel 9 found that the rates of sperm acquisition (median [interquartile range, IQR]) are 45% (24%–68%) in traditional TESE and 63% (42%–81%) in Micro-TESE. Amer et al .…”
Section: Introductionmentioning
confidence: 99%